Age-related functional changes in domain-specific medial temporal lobe pathways - Berron, David; Neumann, Katja; Maass, Anne; Schütze, Hartmut; Fliessbach, Klaus; Kiven, Verena; Jessen, Frank; Sauvage, Magdalena; Kumaran, Dharshan; Düzel, Emrah (Neurobiology of aging, 2018)
There is now converging evidence from studies in animals and humans that the medial temporal lobes (MTLs) harbor anatomically distinct processing pathways for object and scene information. Recent functional magnetic resonance imaging studies in humans suggest that this domain-specific organization may be associated with a functional preference of the anterior-lateral part of the entorhinal cortex (alErC) for objects and the posterior-medial entorhinal cortex (pmErC) for scenes. As MTL subregions are differentially affected by aging and neurodegenerative diseases, the question was raised whether aging may affect the 2 pathways differentially. To address this possibility, we developed a paradigm that allows the investigation of object memory and scene memory in a mnemonic discrimination task. A group of young (n = 43) and healthy older subjects (n = 44) underwent functional magnetic resonance imaging recordings during this novel task, while they were asked to discriminate exact repetitions of object and scene stimuli from novel stimuli that were similar but modified versions of the original stimuli (“lures”). We used structural magnetic resonance images to manually segment anatomical components of the MTL including alErC and pmErC and used these segmented regions to analyze domain specificity of functional activity. Across the entire sample, object processing was associated with activation of the perirhinal cortex (PrC) and alErC, whereas for scene processing, activation was more predominant in the parahippocampal cortex and pmErC. Functional activity related to mnemonic discrimination of object and scene lures from exact repetitions was found to overlap between processing pathways and suggests that while the PrC-alErC pathway was more involved in object discrimination, both pathways were involved in the discrimination of similar scenes. Older adults were behaviorally less accurate than young adults in discriminating similar lures from exact repetitions, but this reduction was equivalent in both domains. However, this was accompanied by significantly reduced domain-specific activity in PrC in older adults compared to what was observed in the young. Furthermore, this reduced domain-specific activity was associated to worse performance in object mnemonic discrimination in older adults. Taken together, we show the fine-grained functional organization of the MTL into domain-specific pathways for objects and scenes and their mnemonic discrimination and further provide evidence that aging might affect these pathways in a differential fashion. Future experiments will elucidate whether the 2 pathways are differentially affected in early stages of Alzheimer's disease in relation to amyloid or tau pathology.